2015
DOI: 10.1074/jbc.m114.625509
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Na+ Affinity in Aspartate 928 Mutants of Na+,K+-ATPase by Secondary Mutation of Glutamate 314

Abstract: Background: Mutation of the aspartate associated with Na ϩ site III of Na ϩ ,K ϩ -ATPase causes neurological disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(14 reference statements)
1
13
0
Order By: Relevance
“…This seems to be in accord with the free energy perturbation calculations done by Rui et al (14) demonstrating that the charge neutralizing the D926N mutation eliminates Na ϩ selectivity. In fact, D926N mutants have a decreased apparent Na ϩ affinity, despite a slight E1/E2 conformational shift toward E1 (33). For the outward-facing K ϩ sites, pK a estimations suggest that increasing pH results in deprotonation of Asp 926 and perhaps Glu 327 .…”
Section: Discussionmentioning
confidence: 99%
“…This seems to be in accord with the free energy perturbation calculations done by Rui et al (14) demonstrating that the charge neutralizing the D926N mutation eliminates Na ϩ selectivity. In fact, D926N mutants have a decreased apparent Na ϩ affinity, despite a slight E1/E2 conformational shift toward E1 (33). For the outward-facing K ϩ sites, pK a estimations suggest that increasing pH results in deprotonation of Asp 926 and perhaps Glu 327 .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of characteristic leak current with mutations in site III revealed that the Na + binding affinity in Asp926 mutants are less sensitive to extracellular sodium, whereas Glu954 mutations cause less leakage57. Although a recent study suggests that Asp926 coordinates site III, the role of Asp926 is described as “relatively minor” in mutagenesis experiments58. However, our six best candidates for the most stable Na + bound protonation states suggest that at least one proton should be available to each Na + binding site.…”
Section: Resultsmentioning
confidence: 99%
“…The water molecule movement through each pathway was calculated as described in the Supporting Information. There are three water pathways in the NKA, including the contentious C-terminal pathway1458, and each pathway is closely related to the acidic residues around each binding site. The extracellular pathway is near site I and two intracellular pathways, N- and C-terminal pathway are near site II and site III, respectively1214 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SigmaPlot program (SPSS, Inc.) was used to fit the relevant equations to data points using nonlinear regression (48). The Na ϩ and ATP dependences of the ATPase activity or phosphorylation were fitted by the following Hill function.…”
Section: Biochemical Experimentsmentioning
confidence: 99%